Coronets and Altars: Aristocratic Women’s and Men’s Support for the Oxford Movement in Scotland during the 1840s - Strong, Rowan (Studies in church history, 1998)
The Oxford Movement has been portrayed in its classic historiography as both clericalist and, in so far as all nineteenth-century Anglican clergy were male, a movement of masculine leadership and initiatives. This is not to deny that the movement was largely priest-led and therefore male in its leadership but ‘largely’ does not mean ‘exclusively’. By looking at the introduction of the Oxford Movement into Scotland, a neglected aspect of its dissemination can be restored, that is, the importance of the laity and of women in the spread of Tractarianism. In Scotland the initial impetus given to Oxford Movement ideals and projects lay not with the clergy but with the aristocratic laity. It also was not the preserve of men, for among its first great supporters in Scotland was a woman, Cecil Chetwynd, widow of John William Robert Kerr, seventh Marquess of Lothian. She would become one of the leading Scottish Tractarians during the 1840s until her conversion to Roman Catholicism in 1851 as a consequence of the Gorham judgement.